Quality Control Standardization and Evaluation of Antimicrobial Potential of Daruhaldi (Berberis aristata DC) Stem Bark. (2nd January 2020) - Khan, Mohammad Irfan; Rahman, Md. Azizur; , Badruddeen; Khalid, Mohammad; Khushtar, Mohammad; Mujahid, Md.
Abstract: Berberis aristata is used for the treatment of diabetes, piles, and liver diseases. As the drug is broadly used in Indigenous systems of medicine, it was designed to set the quality standards and antimicrobial potential for the stem bark of Berberis aristata . Botanical, physicochemical, pharmacotoxicological, fluorescence, microbial load, and phytochemical parameters of the stem bark were determined. High-performance thin-layer chromatography (HPTLC) was carried out by the CAMAG-HPTLC system. Berberine, total phenolics, and flavonoids were estimated. The antimicrobial potential was determined against the bacteria Bacillus subtilis and Escherichia coli and fungi Penicillium citrinum and Aspergillus terreus . The foreign matter, foaming index, swelling index, bitterness value, resin content, loss on drying, total ash, acid-insoluble ash, water-soluble ash, heavy metals, microbial load, berberine content, total phenolic content, and total flavonoid content were found to be 0, 0, 5, 1.34, 0.86%, 2.07%, 4.33%, 0.28%, 2.66%, within limits, 6 colonies in 1/100 dilution, 0.032 mg/g, 144.04 µg/ml, and 85.61 µg/ml, respectively. Phytochemicals such as phenolics, flavonoids, and sterols were present in the methanolic extract. The fluorescences observed in UV light were of different colors in different solvents. The methanolic extract and standards exhibited antimicrobial activity at the tested concentrations against the microbial strains. Results confirmed the quality and purity of the drug B. aristata . Results also confirmed that methanolic extract of B. aristata stem bark possesses potent antimicrobial activity. Thus, the use of this quality-controlled plant-derived drug with established antimicrobial property could be of great significance in quality-control standardization and preventive and therapeutic approaches to infectious diseases.